Konstruksi Makna Kecerdasan Buatan dalam Iklan Digital: Analisis Semiotika Roland Barthes dan Perspektif Strategi Komunikasi PR pada Iklan Gemini Canvas @googleindonesia - Andika Dwi Eranggani; Dewi Mentari (Universitas Palangka Raya, 2026)
The development of artificial intelligence (AI) has fundamentally transformed digital marketing communication, while emerging as a strategic instrument in public relations practices of global corporations. This study aims to examine the construction of meaning around artificial intelligence as a financial solution within the cultural context of Lebaran, while analyzing the PR communication strategy employed by Google Indonesia in building persuasive messages for its public on digital platforms. The research object is a video advertisement posted on the official Instagram account @googleindonesia on March 7, 2025, promoting the Gemini Canvas feature for managing Tunjangan Hari Raya (THR) budgets. This study employs a descriptive qualitative approach with an interpretive paradigm, integrating two complementary analytical perspectives: first, Roland Barthes three-level semiotic analysis — denotation, connotation, and myth — to deconstruct meaning constructed through visual, verbal, and auditory signs in the advertisement; second, the PR communication strategy framework from Smith (2021) to identify how the choices of mascot, emotional message, and cultural appeal represent strategically planned communication decisions by Google Indonesia. The findings reveal that Google Indonesia constructs Gemini Canvas as an empathetic and culturally aware entity through three key elements: anthropomorphic symbolism in the form of a bespectacled cat functioning as brand mascot, local cultural markers of ketupat and THR, and Arabic-nuanced music that aurally reinforces the Lebaran atmosphere — all representing deliberate strategic PR decisions. From Smith’s (2021) perspective, the advertisement applies a proactive communication strategy combining negative emotional appeal — financial anxiety ahead of THR — immediately followed by positive emotional appeal as a concrete solution through Gemini Canvas, representing a structured form of public perception shaping. At the myth level, the advertisement normalizes reliance on digital platforms through systematic cultural localization. This study contributes to understanding AI-based digital marketing communication strategies and the shaping of public perception on AI technology by global corporations in the Indonesian market.